PERILAKU KEKERASAN PADA PERAWAT DI RUANG PERAWATAN JIWA - Rahma Yulis; Esse Puji Pawenrusi; Nurul Amalia; Rasmawati Rasmawati (Universitas Islam Negeri Alauddin Makassar, 2023)
Nurses are vulnerable to violent behavior, especially in the psychiatric ward. Objective: identify violent behavior that is often experienced by nurses and the factors that influence it. Method: using a cross sectional design with an analytic observational approach. The research was conducted at X Hospital in the psychiatric ward: Psychiatry High Care Unit, adult women, men with criminal case and two rooms for men without criminal cases. Sample consisted of 63 nurses through a purposive sampling technique. The instrument used was the Perception of Prevalance of Aggression Scale (POPAS). Data analysis with univariate and bivariate through chi square test with p<0.05. Results: the most violent behavior of patients towards nurses was verbal then physical and sexual violence. There were significant differences in violent behavior received by male and female respondents, such as: provocative and physical threats. There were significant differences in violent behavior based on the type of psychiatric ward such us: nagging, insulting, threats, humiliation to nurses, provocative, physical threats, physical violence that caused minor and serious injuries. Minor injuries were more experienced by male. Sexual temptation is more experienced by women, especially in adult men's treatment rooms, both with and without criminal cases. Conclusion: the most violent behavior of patients towards nurses in psychiatric ward was verbal then physical and sexual violence. There were significant differences in violent behavior based on gender and the type of psychiatric ward. More minor injuries were experienced by male, while sexual temptation was experienced more by women, especially in adult male rooms.